The effect of body weight on intravenous diltiazem in patients with atrial fibrillation with rapid ventricular response. (28th June 2018) - Zimmerman, D. E.; Jachim, L.; Iaria, A.; Brun, C.; Covvey, J. R.
Summary: What is known and objectives: To assess the effect of body weight on the total dose of intravenous (IV) diltiazem needed to reach goal heart rate (HR) for atrial fibrillation (Afib) with rapid ventricular response (RVR) in the emergency department (ED) setting. Methods: A single‐center retrospective cohort was ascertained using electronic medical record data from January 2013 to December 2016. Inclusion criteria consisted of new onset Afib with RVR, receipt of IV diltiazem in the ED, and age ≥18 years old. The primary outcome was the total dose of diltiazem needed to reach goal HR <100, stratified by patients who were <100 kg and those ≥100 kg. The secondary outcome was the total time required to reach goal HR. Demographic, clinical and medication‐related data were collected, including selected safety endpoints. Results and discussion: A total of 328 patients were included. Patients required a mean of 30.1 mg (±24.6) of diltiazem and 2.3 hours (±2.9) to reach goal HR. The total dose of diltiazem was similar for patients <100 kg and ≥100 kg (28.7 vs 34.3 mg; P  = .068) as was the time to reach goal HR (2.3 vs 2.3 hours; P  = .949), respectively. No differences were noted in incidence of hypotension, bradycardia or need for additional rate control agents. What is new and conclusion: No difference in the total amount of diltiazem or time to reach goal HR was found in patients according to body weight stratification. Abstract : This analysis of diltiazem for patients with atrial fibrillation with rapid ventricular response in a single urban medical centre found no difference in the total amount of diltiazem or time to reach goal heart rate in patients who were <100 kg compared to ≥100 kg of total body weight